Polymerase chain reaction with two molecular targets in mucosal leishmaniasis' diagnosis: a validation study - Clemencia Ovalle Bracho; Luisa Porras de Quintana; Sandra Muvdi Arenas; Melania Rios Parra (Memorias do Instituto Oswaldo Cruz, 2007)
We validated the polymerase chain reaction (PCR) with a composite reference standard in 61 patients clinically suspected of having mucosal leishmaniasis, 36 of which were cases and 25 were non-cases according to this reference standard. Patient classification and test application were carried out independently by two blind observers. One pair of primers was used to amplify a fragment of 120 bp in the conserved region of kDNA and another pair was used to amplify the internal transcript spacers (ITS) rDNA. PCR showed 68.6% (95% CI 59.2-72.6) sensitivity and 92% (95% CI 78.9-97.7) specificity; positive likelihood ratio: 8.6 (95% CI 2.8-31.3) and negative likelihood ratio: 0.3 (95% CI 0.3-0.5), when kDNA molecular target was amplified. The test performed better on sensitivity using this target compared to the ITS rDNA molecular target which showed 40% (95% CI 31.5-42.3) sensitivity and 96% (95% CI 84.1-99.3) specificity; positive likelihood ratio: 10 (95% CI 2.0-58.8) and negative likelihood ratio: 0.6 (95% CI 0.6-0.8). The inter-observer agreement was excellent for both tests. Based upon results obtained and due to low performance of conventional methods for diagnosing mucosal leishmaniasis, we consider PCR with kDNA as molecular target is a useful diagnostic test and the ITS rDNA molecular target is useful when the aim is to identify species.